Pengaruh Kualitas Pelayanan dan Inovasi Pelayanan terhadap Kepuasan Pasien di Puskesmas Mekar Mukti Cikarang Utara - Tamba, Rousdy Safari; Hartono, Hartono; Mirnawati, Mirnawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aims to analyze the Effect of Service Quality and Service Innovation on Patient Satisfaction at the Mekar Mukti Health Center in North Cikarang. This research method is to use quantitative research methods and data analysis methods using multiple linear regression. Data analyzer uses data processing software SPSS 24 for windous. The study population was patients who visited the Mekar Mukti Health Center. Stamp in this study using Hair et al, amounting to 115 respondents.The results of this study indicate that the independent variable that is Service Quality has a positive and significant effect of 56.4% on Patient Satisfaction, the Service Innovation variable has no significant effect of 38.8% on Patient Satisfaction, and the Service Quality and Service Innovation variables simultaneously influence on Patient satisfaction with a contribution of 57,8% the remaining 42,2% is influenced by other factors not examined in this study.